2021
DOI: 10.1002/smll.202103984
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Derived Biogenetic Gold Nanoparticles for Sensitizing Radiotherapy and Boosting Immune Response against Cancer

Abstract: The biosynthesis of nanomedicine has gained enormous attention and exhibited promising prospects, while the underlying mechanism and advantage remain not fully understood. Here, a cell‐reactor based on tumor cells is developed to obtain biogenetic gold nanoparticles (Au@MC38) for sensitizing radiotherapy and boosting immune responses. It demonstrates that the intracellular biomineralization and exocytosis process of Au@MC38 can be regulated by the cellular metabolites level and other factors, such as glutathio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…Zhang et al . revealed that the intracellular synthesis of gold NPs was a complex process and was modulated by various factors, such as glutathione (GSH) and ROS . The precise mechanism of endocytosis and efflux of AIEgens from the DC reactor is not well understood thus far and deserves our further intensive investigation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al . revealed that the intracellular synthesis of gold NPs was a complex process and was modulated by various factors, such as glutathione (GSH) and ROS . The precise mechanism of endocytosis and efflux of AIEgens from the DC reactor is not well understood thus far and deserves our further intensive investigation.…”
Section: Resultsmentioning
confidence: 99%
“…31 Zhang et al revealed that the intracellular synthesis of gold NPs was a complex process and was modulated by various factors, such as glutathione (GSH) and ROS. 28 The precise mechanism of endocytosis and efflux of AIEgens from the DC reactor is not well understood thus far and deserves our further intensive investigation. Dynamic light scattering (DLS) detection exhibited the sizes of isolated DEV-AIE and DEVs were 131.14 ± 5.25 nm and 92.73 ± 5.14 nm, and the corresponding PDI values were 0.249 and 0.275, respectively (Figure 2C and Table S2).…”
Section: Synthesis and Characterization Of Mbpn-tcypmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to delivering small molecule drugs, TEXs can be manipulated to load gold nanoparticles. For example, tumor cells can be cultured in a medium containing HAuCl 4 solution, and the cells can be used to synthesize gold nanoparticles and release them directly as TEX-encapsulated gold nanoparticles (Au@MC38) [ 151 ] ( Fig. 3 C and D).…”
Section: Tumor-derived Extracellular Vesicles (Tevs)mentioning
confidence: 99%
“…A Clinical study has confirmed that the oxygen content of tumor cells has a great effect on the killing effect of radiation (4). This is because the high-energy ionizing radiation generated during RT can produce reactive oxygen species (ROS) in the aerobic microenvironment, which in turn damage the normal structure of tumor deoxyribonucleic acid (DNA) and cause tumor cell death (4,5). Thus, the therapeutic effect of RT is positively correlated with the partial pressure of oxygen inside the solid tumor.…”
Section: Introductionmentioning
confidence: 99%